Foods, Dietary Patterns and Occupational Class and Leukocyte Telomere Length in the Male Population. Issue 2 (March 2018) - Karimi, Behrooz; Nabizadeh, Ramin; Yunesian, Masud; Mehdipour, Parvin; Rastkari, Noushin; Aghaie, Afsaneh
Telomeres contain TTAGGG repetitive sequences and are located at the end of human chromosomes. Telomere dysfunction is associated with some age-related and chronic diseases, but its relationship with foods, dietary patterns, and occupational class in the young male population is not yet known. In this cross-sectional study, 300 healthy men, residents of Tehran, aged 25–40 years were enrolled from January to December 2016. We employed a cross-sectional study of 300 healthy people, residents of Tehran, aged 25-40 years. A food frequency questionnaire was used to obtain food intakes of all participants and converted into actual food intake (g/day). The principal components analysis was used to determine dietary patterns and other demographic characteristics. Leukocyte telomere length (TL) was measured by quantitative real-time polymerase chain reaction (PCR) to measure number of telomere repeat copy number (T) to the relative number of 36B4 copies (S) (T/S ratio). T/S in office-workers, waste recyclers, and other workers were 1.22 ± 0.4, 1.08 ± 0.3, and 1.094 ± 0.34, respectively. The results of multivariate linear regression adjusted for age, body mass index (BMI), and smoking were showed that whole grains (β = 0.02; p = .05), refined grains, fruits and vegetables, fish and dairy products were associated with an increase in log-T/S, but consumption of nuts and seeds (β = −0.00072; p = .06), meats (β = −0.00043; p = .9), produced meats (β = −0.00238; p = .03), oils and solid fats (β = −0.00146; p = .03) had a negative relationship with log-T/S in all studied occupational classes. A positive relationship was reported between the healthy (β = 0.017; p = .2) and traditional dietary pattern (β = 0.012; p = .4) with log-T/S, but western pattern identified negative relationship (β = −0.004; p = .7). Adherence to a healthy (with consumption whole grains, refined grains, dairy, and cereals) and then traditional pattern with increased consumption of fruits, vegetables and whole grains, fish and dairy products are necessary to prevent TL destruction in all studied occupational classes.